High-Performance Blue Quantum Dot Light Emitting Diode via Solvent Optimization Strategy for ZnO Nanoparticles - Ji Xu; Lixi Wang; Xueliang Zhao; Yutong Shi; Yongjiao Shi; Ting Liu (Nanomaterials, 2021)
Here, we report on the high-performance blue quantum dots (QDs) light-emitting diodes (QLEDs), in which the ZnO nanoparticles (NPs) are employed as the electron transport layer (ETL) and optimized with different alcohol solvents. The experimental results demonstrate that the properties of solvent used for ZnO NPs—such as polarity, viscosity and boiling point—play a crucial role in the quality of film where they modulate the electron injection across the QDs/ETL interface. The maximum current efficiency of 3.02 cd/A and external quantum efficiency (EQE) of 3.3% are achieved for blue QLEDs with ZnO NPs dispersed in butanol, exhibiting obvious enhancement compared with the other solvents. This work provides a new method to select proper solvent for ETL which can further improve the device performance.